A Composite Measure of Gender and Its Association With Risk Factors in Patients With Premature Acute Coronary Syndrome. Issue 5 (June 2015) - Pelletier, Roxanne; Ditto, Blaine; Pilote, Louise
ABSTRACT Objective To create a gender index by using principal component analyses (PCA) and logistic regression, and to determine the association between gender, sex, and cardiovascular risk factors among patients with premature acute coronary syndrome (ACS). Methods GENESIS-PRAXY is a cohort study including ACS patients aged 55 years or below, and with ACS recruited between 2009 and 2013 from 26 centres across Canada, the United States, and Switzerland. A sample of 1075 patients was used for this study. Psychosocial variables assumed to differ between sexes (i.e., gender related) were included in PCA. Variables identified on retained components were included in logistic regressions where coefficient estimates of variables associated with sex were used to calculate a gender score. Cardiovascular risk factors were assessed using self-report and chart review data. Results After the inclusion of 26 psychosocial variables in PCA, we identified 17 variables within retained components; 7 of which were associated with sex in logistic regression. The gender distribution revealed that half of women had a more androgyne or masculine gender score, and 16% of men exhibited a more feminine gender score. In univariable analyses, feminine gender scores and female sex were associated with hypertension, diabetes, family history of cardiovascular disease (only gender), and depressive/anxious symptoms. In multivariable models including both gender score and sex, feminine gender score but not female sex was associated with the presence of risk factors. Conclusions Sex and gender are distinct constructs, and the derived gender index offers a current and pragmatic option to measure gender within ACS populations. Our results further suggest that traditional sex differences in cardiovascular disease risk factors may be partly explained by patient's gender-related characteristics.